Woodchip transportation: Climatic and congestion influence on productivity, energy and CO2 emission of agricultural and industrial convoys. (August 2017) - Manzone, Marco; Calvo, Angela
Abstract: Aim of this study is to analyze the energy requirements and the CO2 emission of the wood chip transportation in a short supply chain (within a radius of the travelled distance equal to 70 km), using two different types of vehicles: agricultural and industrial convoys. Three itineraries (located in North-West of Italy) with different length (14.5, 36.5 and 68.5 km) but similar in route characteristics were travelled by both the convoys in three different traffic conditions (morning, afternoon and evening) and in two different road states (dry and wet). The energy balance was always positive (from 48 to 335) and truck values were about twice than tractor. The specific energy was directly proportional to the itinerary length and the lowest values were observed in the shortest itinerary (9.44 MJ m −3 for the truck and 17.19 MJ m −3 for the tractor). The net energy highlighted similar values for both convoys (3350 MJ m −3 ). The CO2 eq. emission per volume unit transported ranged from 0.94 to 8.53 kg m −3, while per kilometer travelled it varied between 1.33 and 4.24 kg km −1 . The truck is more efficient than the tractor, especially in dry road conditions, but it was less versatile. Highlights: Agricultural and industrial vehicles were considered for woodchips transportation. The energy balance is always positive and for the truck it is twice than the tractor. The energy spent depend by the distance and the considered convoy. The truck is more efficient than the tractor, especially in dry road conditions. In CO2 eq emission the truck always showed values lower than the tractor.